2021
DOI: 10.1158/1078-0432.ccr-20-4532
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Controlled Trial Comparing Two Different Schedules for Cisplatin Treatment in Patients with Locoregionally Advanced Nasopharyngeal Cancer

Abstract: Cisplatin based concomitant chemoradiotherapy is the standard treatment modality for patients with locoregionally advanced nasopharyngeal carcinoma (NPC), though current schedule and dose of cisplatin is not optimal. Mounting retrospective evidence indicate that a cumulative dose of cisplatin with 200 mg/m2 could obtain acceptable survival benefit. However, there is no prospective study to provides high-level evidence and clarify the efficacy of this therapeutic strategy so far. Our study is the first phase II… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 36 publications
(90 reference statements)
0
18
0
Order By: Relevance
“…A recent report from China found that leukopenia and thrombocytopenia were more frequent in a weekly cisplatin arm compared with a 3-weekly cisplatin arm although the planned total dose of the weekly cisplatin arm was higher than that of the 3-weekly arm (240 mg/m 2 v 200 mg/m 2 ). 31 While recognizing this difference, these findings indicate the need for care in avoiding hematologic toxicities in the safety management of this regimen. More particularly, they suggest the importance to safety of dose selection, which takes account of both total and individual dosage.…”
Section: Discussionmentioning
confidence: 99%
“…A recent report from China found that leukopenia and thrombocytopenia were more frequent in a weekly cisplatin arm compared with a 3-weekly cisplatin arm although the planned total dose of the weekly cisplatin arm was higher than that of the 3-weekly arm (240 mg/m 2 v 200 mg/m 2 ). 31 While recognizing this difference, these findings indicate the need for care in avoiding hematologic toxicities in the safety management of this regimen. More particularly, they suggest the importance to safety of dose selection, which takes account of both total and individual dosage.…”
Section: Discussionmentioning
confidence: 99%
“…Given this evidence, updated reviews and guidelines recommended that a cumulative cisplatin dose of 200 mg/m 2 may be the optimal threshold . A recent study has shown that 2 cycles of triweekly cisplatin, 100 mg/m 2 , was noninferior to standard weekly cisplatin, 40 mg/m 2 , for patients with locoregionally advanced NPC . Another updated randomized phase 2 noninferiority trial also revealed that 2 cycles of triweekly cisplatin, 100 mg/m 2 , was noninferior to 3 cycles for patients with Epstein-Barr virus DNA levels of less than 4000 copies/mL …”
Section: Discussionmentioning
confidence: 99%
“…Characteristics of the selected studies are summarized in Table 1 . Six retrospective studies ( Jagdis et al, 2014 ; Tao et al, 2014 ; Meng et al, 2018 ; Zhu et al, 2018 ; Wang et al, 2019 ; Gundog et al, 2020 ) and two RCTs ( Lee et al, 2016 ; Xia et al, 2021 ) were included in the analysis. The RCTs included one phase II and one phase III clinical trials.…”
Section: Resultsmentioning
confidence: 99%